Pengaruh Rasio Keuangan Early Warning System Terhadap Tingkat Solvabilitas Pada Perusahaan Asuransi Yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2020 - Emia Fepa Yosa; Sri Rahayu; Shofwan Andri; Heny Triastuti Kurnia Ningsih (Universitas Islam Islam Sumatera Utara, 2022)
Early Warning System is a tool that can be used to analyze financial statements and process them into useful information to be used as a monitoring system for the financial performance of the insurance company concerned. This study aims to examine the ratio of liquidity ratios, claims expense ratios, and the ratio of premium growth to solvency levels as proxied by Risk Based Capital (RBC). The population in this study were 16 insurance companies listed on the Indonesia Stock Exchange (IDX). The sample used is 10 companies obtained by using purposive sampling method. The data obtained from the analysis of the company's annual report obtained from the IDX's official website, namely www.idx.co.id with the data method using the classical assumption test, multiple linear regression test, hypothesis testing, and coefficient of determination test. The results of the study show that: (1) Liquidity has a positive and significant effect on risk based capital; (2) The claim expense ratio has a positive and significant effect on risk based capital; (3) Premium growth has a positive and significant effect on risk based capital. Based on the F test, liquidity, claims expense ratio, and premium growth have a positive and significant effect on risk based capital.